The barriers of the implementation of lean construction in Klang Valley, Malaysia - Ahmed M.E.A.; Wong L.S. (IOP Publishing Ltd, 2023)
The traditional procurement system, the structure of the industry and the nature of the construction product all influence current practices and thinking within the construction industry. Whilst there have been recent changes in the way the industry operates, the majority of construction projects in Klang Valley are still delivered using traditional practices. The objective of this paper is to evaluate the influence factors of the implementation lean construction at selected construction sites in Klang Valley, Malaysia. Evaluation index system in terms of questionnaire and interview were utilized to evaluate the barriers of the implementation of lean construction. Based on that, questionnaire was selected with workers to evaluate the implementation of lean construction techniques in Klang Valley. After that, interview was selected to study the influence factors on the implementation of lean construction. Structural Equation Modelling was utilized in the survey with the project team (contractors, clients and consultants) to measure the effectiveness of the barriers and strategies of the implementation of lean construction at the construction sites. Based on that, the strategies of the implementation of lean construction can be described as follows. Provide support from the top management, develop strategic alliance between various firms, A requirement of staff competent to lean construction, develop the integration between design and construction, educate people about lean construction, encourage clients to adopt lean construction, provide staff training about lean construction as well as disputes and claims. In addition, their standardized estimates (SE) are ( = 0. 013, 0.025, 0.023, 0.027, 0.015, 0.034, 0.021, 0.021, 0.023 respectively. Published under licence by IOP Publishing Ltd.